What has changed in the prevalence of hypertension in dialyzed children during the last decade?. (1st January 2017) - Tkaczyk, Marcin; Stańczyk, Małgorzata; Miklaszewska, Monika; Zachwieja, Katarzyna; Wierciński, Ryszard; Stankiewicz, Roman; Firszt-Adamczyk, Agnieszka; Zachwieja, Jacek; Borzęcka, Halina; Zagożdżon, Ilona; Leszczyńska, Beata; Medyńska, Anna; et al.
Abstract: Background: Hypertension very often accompanies progression of chronic kidney disease (CKD) in children. A cross-sectional analysis of hypertension prevalence in dialyzed children in Poland was designed with a comparison with the data previously recorded 10 years earlier. Methods: Two cohorts of children were analyzed: 59 subjects dialyzed in 2013, and 134 children from the previous study performed in 2003 that were reevaluated according to the current methodology. The incidence of hypertension (defined by SDS of sBP or dBP >1.64), clinical data, medical history, dialysis modalities and selected biochemical parameters of dialysis adequacy were analyzed. Results: The prevalence of hypertension increased from 64% in 2003 to 78% in 2013. The efficacy of antihypertensive treatment remained unsatisfactory (61% proper BP control). Preservation of residual urine output and strict fluid balance may prevent development of hypertension in children on dialysis. Conclusions: Despite the higher awareness of hypertension and its complications in dialyzed children, the incidence of this entity has increased during the last decade, with the percentage of undertreated patients comparable to that observed 10 years ago. Thus, more attention should be paid to therapy efficacy in this population to prevent further damage to the cardiovascular system and to decrease morbidity.